Is knowledge that powerful? Financial literacy and access to finance: An analysis of enterprises in the UK - Hussain, J.; Salia, S.; Karim, A. (Journal of Small Business and Enterprise Development, 2018)
Purpose The purpose of this paper is to examine the relationship between financial literacy, access to finance and growth among small- and medium-sized enterprises (SMEs) within the Midlands region of the UK. It assesses whether financial literacy assists SMEs to overcome information asymmetry, mitigates the need for collateral, optimizes capital structure and improves access to finance. Design/methodology/approach To gain a deeper insight into the complex relationship between financial literacy, access to finance and growth, a qualitative research is carried out among SMEs that have operated for over five years or longer. Using the purposive sampling technique, 37 firms were selected based on size, location and characteristics, mainly from the city of Birmingham and the joining conurbations. Open-ended and a combination of dichotomous questions were used for the survey. Interviews were recorded, transcribed and thematically analyzed. Findings Financial literacy is an interconnecting resource that mitigates information asymmetry and collateral deficit when evaluating loan applications, therefore financial literacy should be part of school curriculum. The analysis suggests enhanced financial literacy, reduces monitoring cost and serves to optimize firms’ capital structure that positively impacts on SMEs growth. Financial management knowledge is recognized as the core resource that aids an effective decision making by owners of SMEs. Research limitations/implications The limitation of this research is the small sample that limits its generalization. Its findings could be enhanced by a larger sample and by conducting comparative studies in other regions or economies. SMEs growth is seen as a strategic policy to stimulate enterprise but the finance gap tends to constrain that objective. The UK Government’s effort to improve access to finance and to mitigate excessive collateral demands by lenders has proved elusive. This empirical research provides evidence that financial literacy enhances access to finance and, in turn, promotes growth potentials. Practical implications The results of this study advocate the provision of financial literacy at schools and target support for SMEs to acquire financial management skills in order to mitigate information asymmetry between lenders and borrowers. Social implications Findings suggest that financial literacy mediates access to finance, enables enterprises to use optimal financial structure to mitigate business failure, creates employment and reduces public sector support for social benefits. Originality/value This study is novel in that it examines financial literacy and its implications for access to finance and firm growth in the UK. The study is an effort to highlight the role of financial information in mitigating barriers to finance for SMEs.
Keywords: SMEs; Growth; Financial literacy; Access to finance